DNA flow cytometric evaluation of cell cycle distribution in ulcerative colitis: a proposed method for assessing severity of disease. Issue 1 (January 1995) - Bortoluzzi, F; Valentini, M; Cernigoi, C; Toffoli, G; Boiocchi, M; Poletti, M; Sozzi, M; Fornasarig, M; Cannizzaro, R; Bertolissi, E
Abstract : The assessment of disease severity in ulcerative colitis depends mainly on subjective variables, and an objective method of assessing mucosal inflammation is needed. Determination of the synthetic phase of the cell cycle is an accurate expression of inflammatory activity in the colonic mucosa. The aim of the study was to find out if the proliferative index or the synthetic phase (S phase) of the colonic mucosa of patients with ulcerative colitis, as evaluated by DNA flow cytometry, is a reliable and reproducible marker of disease activity. Sixty consecutive patients with ulcerative colitis of different degrees of activity were entered into the study and submitted to colonoscopy plus multiple rectal biopsies. Disease severity was defined for each patient by means of a clinical, endoscopic, and histological score. Flow cytometry was used to calculate the proliferative index and the S phase of the cell cycle. A statistically significant correlation (p < 0.001) was found between all indices of severity. It is suggested that flow cytometric evaluation of the cell cycle in the rectal mucosa may be an efficient method of assessing severity of disease and efficacy of medical treatment in ulcerative colitis.